2017
DOI: 10.1016/j.jfluidstructs.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Pursing of planar elastic pockets

Abstract: The pursing of a simply-or doubly-connected planar elastic pocket by an applied pressure is analysed from the bending to the stretching regimes. The response is evaluated in terms of maximum deflection and profiles across a range of simply-and doubly-connected circular and square shapes. The study is conducted using experimental and numerical methods and supported by previous analytical results. The experimental method is based on an original 2D optical method that gives access to the pursing direction perpend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…We have also performed studies and developed theoretical models that explain how the appearance of subconjunctival blebs in the early postoperative period may be used to develop clinical grading systems to help improve surgical outcomes following surgery (Bouremel Y, et al IOVS . 2017;58:ARVO E-Abstract 5576) 15. These pressure spikes did not occur in all eyes, and further studies are currently underway to shed more light on why these results were observed.…”
Section: Discussionmentioning
confidence: 88%
“…We have also performed studies and developed theoretical models that explain how the appearance of subconjunctival blebs in the early postoperative period may be used to develop clinical grading systems to help improve surgical outcomes following surgery (Bouremel Y, et al IOVS . 2017;58:ARVO E-Abstract 5576) 15. These pressure spikes did not occur in all eyes, and further studies are currently underway to shed more light on why these results were observed.…”
Section: Discussionmentioning
confidence: 88%
“…Full numerical calculations confirm that the above model is good when λ 0 ≤ 1.1 (Bouremel et al, 2017), beyond which the analysis breaks down since the increase of λ 1 withr needs to be taken into account. When the pocket is compressed, within the contact region λ 1 = λ 2 = λ c are constants, while outside the contact-region, we approximate the stretch factors as…”
Section: Analytical Modelmentioning
confidence: 70%
“…The material properties were characterised using an electromagnetic linear actuator (Bose Electroforce 3220 Series III to determine C 1 , C 2 and E). The experimental procedure is described in Bouremel et al (2017) and the samples used are different. The Mooney-Rivlin parameters of the silicone sheets are listed in Table 1.…”
Section: Materials Characterisationmentioning
confidence: 99%
“…The transition between the two regimes [Eqs. (1b) and (1c)] occurs in the relative pressure range Δp=p e ¼ 5-10, see [42].…”
Section: =3mentioning
confidence: 99%